The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1038/sj.onc.1204066
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of apoptosis by procaspase-2 short isoform: selective inhibition of chromatin condensation, apoptotic body formation and phosphatidylserine externalization

Abstract: Procaspase-2 is one of the cysteine aspartate proteases involved in apoptotic cell death. Alternative splicing of CASP-2 messenger RNA generates a long isoform, procaspase-2L, whose overexpression induces cell death and a truncated isoform, procaspase-2S, whose function remains poorly de®ned. The present study explored the consequences of procaspase-2S overexpression in U937 human leukemic cells exposed to the topoisomerase II inhibitor etoposide as an apoptotic stimulus. Overexpression of procaspase-2S in U93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 60 publications
1
33
0
Order By: Relevance
“…One can argue that the overexpressed shorter caspase-2 isoform may interfere and inhibit death signal transduction, as previously observed in leukemic cells. 35 On the other hand, we have detected in germ cells and in somatic tissue a third alternative transcript, caspase-2SL, whose putative protein does not include the catalytic domain and has a shorter Cterminal than caspase-2S. This isoform as a CARD protein could be involved in protein recruitment.…”
Section: Discussionmentioning
confidence: 85%
“…One can argue that the overexpressed shorter caspase-2 isoform may interfere and inhibit death signal transduction, as previously observed in leukemic cells. 35 On the other hand, we have detected in germ cells and in somatic tissue a third alternative transcript, caspase-2SL, whose putative protein does not include the catalytic domain and has a shorter Cterminal than caspase-2S. This isoform as a CARD protein could be involved in protein recruitment.…”
Section: Discussionmentioning
confidence: 85%
“…Overexpression of the long isoform caspase-2L was shown to induce programmed cell death (Kumar et al, 1994), whereas its decreased expression by antisense technology delayed apoptosis in response to various stimuli (Kumar, 1995;Troy et al, 2000;Droin et al, 2001a). Conversely, overexpression of the short isoform, caspase-2S, could suppress mammalian cell death (Wang et al, 1994;Kumar, 1995;Droin et al, 2001b). Experiments using caspase-2-knockout mice showed that oocytes were resistant to cell death induced by cytotoxic drugs and that B lymphoblasts were resistant to perforin-and granzyme B-induced apoptosis whereas cell death was accelerated in some neuronal populations (Bergeron et al, 1998;Morita et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation, the 48-kDa procaspase-2 is processed in two subunits of 18 and 14 kDa (Li et al, 1997;Colussi et al, 1998a;Paroni et al, 2001). This activation occurs in many cell types in response to various apoptotic stimuli, including growth factor withdrawal, cytotoxic drug or death receptor ligand treatment, and antigen receptor ligation (Harvey et al, 1996;Stefanis et al, 1998;Droin et al, 2001b). Golgin-160 has been identified as a true caspase-2 substrate (Mancini et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…5 From some of these in vitro results, accelerated death of facial motor neurons observed in vivo during the development of…”
Section: Dear Editormentioning
confidence: 99%
“…The long isoform, caspase-2L, is an ubiquitously expressed 48 kDa protein that appears to be instrumental in the triggering of apoptosis, whereas the short isoform, caspase-2S, is a predicted 34 kDa protein that can antagonize cell death when overexpressed. 5 Synthesis of these proteins depends in part on an alternative mRNA splicing event occurring in the 3 0 portion of the pre-mRNA. 6 Exon 9, a 61 bp sequence, is specifically inserted into caspase-2S mRNA, which leads to a premature stop codon at the very beginning of exon 10.…”
Section: Dear Editormentioning
confidence: 99%